Metabolic responses of rice source and sink organs during recovery from combined drought and heat stress in the field - Lawas, Lovely Mae F.; Erban, Alexander; Kopka, Joachim; Jagadish, Krishna S.V.; Zuther, Ellen; Hincha, Dirk K. (Oxford University Press, 2019)
Drought and heat stress effects on rice have been extensively studied, in particular during the sensitive flowering and grain-filling stages. However, in the field these stresses usually occur together because reduced transpirational cooling under drought conditions results in increased plant tissue temperature. In addition, environmental stresses are usually transient and the ability to efficiently recover from stress may be at least as important for overall stress tolerance as the direct stress response itself. Nevertheless, nothing is known about recovery mechanisms after drought and heat stress in rice under field conditions.ResultsWe have used gas chromatography–mass spectrometry–based metabolomics to elucidate the metabolic responses of flag leaves, flowering spikelets, and developing seeds from 3 rice cultivars differing in their drought and heat tolerance to rewatering after stress in the field. Within 60 hours after rewatering, many stress-responsive metabolites returned to their control levels, although recovery was not complete. In addition, control plants showed developmental differences that were revealed by metabolite profiles during 60 hours of post-stress sampling, in particular in developing seeds. Correlation analysis identified several metabolites as marker candidates for the stability of grain yield or quality under conditions of combined drought and heat stress.ConclusionsThe rewatering responses of stressed plants seemed to be a combination of the reversal of stress effects and reinitiation of development after stress relief. The identified potential markers can be useful in efforts to breed stress-tolerant rice germplasm to ensure food availability under changing climate conditions.